Antimicrobial susceptibility profiles of bacterial isolates from burn wound infections: experience at a tertiary care hospital teaching institution - Thomas, Bonnie J.; Arora, Balvinder Singh; Arora, Savita (International Journal of Research in Medical Sciences, 2022)
Background: This study was conducted to know, understand and document the current bacterial isolates and their antimicrobial susceptibility profile in our tertiary healthcare facility. Aim was to isolate, identify and study the current antimicrobial susceptibility profiles of bacterial isolates from patients with burn wound infections admitted in our tertiary care hospital. Methods: Wound swabs from burn patients admitted in burn ICU and burn wards were collected on day 1, day 3, day 5 and day 10. Samples were processed using standard microbiologic procedure and bacterial isolates that grew on culture was tested for their antimicrobial sensitivity pattern using Kirby Bauer disk diffusion method. Results: Majority of patients in this study were of the age group of 21 to 30 years (32%). Total body surface area (TBSA) of the study subjects were collected and it was found that the mean TBSA was 39.59±11.6. Total number of bacterial isolates identified during this study was 226 and of those most common was Klebsiella pneumoniae (n=62). Aminoglycoside resistance were at 61% and among carbapenems, ertapenem showed 90% resistance in Klebsiella pneumoniae isolates. Cefoxitin resistance indicating the presence of MRSA were seen in 31% of Staphylococcus aureus isolates. Acinetobacter showed 100% resistance to ceftazidime. Conclusions: The results indicate the predominance of drug resistant gram-negative bacterial isolates in burn wounds. Klebsiella pneumoniae came out to be the most common bacterial isolate in our study. Because of increasing resistance and decreasing availability of newer antibiotics, active microbial surveillance and judicious antibiotic usage is the way forward.